TEACHERS’ STRATEGIES IN TEACHING READING COMPREHENSION - Fitri Nurdianingsih (IKIP Siliwangi, 2021)
Abstract This study is aimed at portraying teacher’s strategies in teaching reading comprehension to students by involving an English teacher. In collecting the data, interview was conducted to identify the strategies of teaching reading comprehension. The result revealed that the strategies used by the teacher were understanding text, individual and group learning strategy, and QAR strategy. The result indicated that teachers need to be equipped by strategies in teaching reading comprehension in order to help the students to cope with the difficulties in learning English. The choice of strategies was adapted by the teachers with the materials, the syllabus and curriculum. Those strategies were effective in teaching reading comprehension because it can help student to comprehend the text and they could exchange their opinion with their friends. Keywords: teachers’ strategy, reading comprehension